2019
DOI: 10.1021/acsami.8b19093
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Two-Dimensional Material Heterojunction Photodetectors with Ultrahigh Speed and Detectivity

Abstract: Lateral heterojunctions in two-dimensional (2D) materials have demonstrated potential for high-performance sensors because of the unique electrostatic conditions at the interface. The increased complexity of producing such structures, however, has prevented their widespread use. We here demonstrate the simple and scalable fabrication of heterojunctions by a one-step synthesis process that yields photodetectors with superior device performance. Catalytic conversion of a solid precursor at optimized conditions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In such lateral heterojunctions, current flows in accordance with the photogating conduction mechanism (which is also equivalent to the photoconductive mechanism) where electrons are trapped while holes are mobile or vice-versa under an external bias. It has been shown that the transport in lateral heterojunctions based on graphene is primarily due to conduction through paths that encounter the lowest barrier heights and the smallest number of barriers . In other words, the transport is percolative in nature, and, in the present case, this would translate to paths with the least number and widths of grain boundaries that the photogenerated carriers encounter.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In such lateral heterojunctions, current flows in accordance with the photogating conduction mechanism (which is also equivalent to the photoconductive mechanism) where electrons are trapped while holes are mobile or vice-versa under an external bias. It has been shown that the transport in lateral heterojunctions based on graphene is primarily due to conduction through paths that encounter the lowest barrier heights and the smallest number of barriers . In other words, the transport is percolative in nature, and, in the present case, this would translate to paths with the least number and widths of grain boundaries that the photogenerated carriers encounter.…”
Section: Resultsmentioning
confidence: 77%
“…It has been shown that the transport in lateral heterojunctions based on graphene is primarily due to conduction through paths that encounter the lowest barrier heights and the smallest number of barriers. 57 In other words, the transport is percolative in nature, and, in the present case, this would translate to paths with the least number and widths of grain boundaries that the photogenerated carriers encounter. The long-term stability of the present devices is shown in Figure S7.…”
Section: Resultsmentioning
confidence: 80%
“…A lightemitting device designed with lateral WSe 2 -MoS 2 heterostructure exhibited a larger conversion efficiency of 1 m% (the ratio of the emitted photon to the injected carriers) in 70 kw cm −2 than a homojunction device based on monolayer MoS 2 [24]. Furthermore, photodetectors built with lateral heterojunction graphene and thin amorphous carbon films have a high photodetectivity of 10 13 Jones and short response time of sub-100 µs [25]. These devices built with LHSs can potentially be used in future electronic circuits and device applications.…”
Section: Introductionmentioning
confidence: 99%
“…2 Similar to the conventional 3D heterojunctions, two-dimensional (2D) heterojunctions comprise two kinds of nanomaterials with different electron affinities and band gaps. [3][4][5] Consequently, they exhibit excellent optoelectronic performance, which cannot be achieved by the individual nanomaterials. Therefore, 2D heterojunctions provide many new opportunities for tailoring the electronic and transport properties as well as for realizing novel device architectures.…”
Section: Introductionmentioning
confidence: 99%